O‐GlcNAc transferase activates stem‐like cell potential in hepatocarcinoma through O‐GlcNAcylation of eukaryotic initiation factor 4E - Cao, Benjin (J Cell Mol Med, 2019)
O‐GlcNAcylation catalysed by O‐GlcNAc transferase (OGT) is a reversible post‐translational modification. O‐GlcNAcylation participates in transcription, epigenetic regulation, and intracellular signalling. Dysregulation of O‐GlcNAcylation in response to high glucose or OGT expression has been implicated in metabolic diseases and cancer. However, the underlying mechanisms by which OGT regulates hepatoma development remain largely unknown. Here, we employed the lentiviral shRNA‐based system to knockdown OGT to analyse the contribution of OGT in hepatoma cell proliferation and stem‐like cell potential. The sphere‐forming assay and western blot analysis of stem‐related gene expression were used to evaluate stem‐like cell potential of hepatoma cell. We found that the level of total O‐GlcNAcylation or OGT protein was increased in hepatocellular carcinoma. OGT activated stem‐like cell potential in hepatoma through eukaryotic initiation factor 4E (eIF4E) which bound to stem‐related gene Sox2 5'‐untranslated region. O‐GlcNAcylation of eIF4E at threonine 168 and threonine 177 protected it from degradation through proteasome pathway. Expression of eIF4E in hepatoma was determined by immunostaining in 232 HCC patients, and Kaplan‐Meier survival analysis was used to determine the correlation of eIF4E expression with prognosis. High glucose promoted stem‐like cell potential of hepatoma cell through OGT‐eIF4E axis. Collectively, our findings indicate that OGT promotes the stem‐like cell potential of hepatoma cell through O‐GlcNAcylation of eIF4E. These results provide a mechanism of HCC development and a cue between the pathogenesis of HCC and high glucose condition.